Competing for attention on digital platforms: The case of news outlets - Meyer, Tim; Kerkhof, Anna; Cennamo, Carmelo; Kretschmer, Tobias (Strategic Management Journal, 2024)
Abstract Research Summary Platforms are often assumed to benefit firms, especially smaller ones, by facilitating access to a broader consumer base and increasing visibility. However, this logic relies on platforms” ability to match consumer preferences to complement characteristics. In addition to this matching mechanism, we posit that platforms also broker consumer attention towards complements, which then compete for this attention. We propose that this attention mechanism is particularly prominent in settings where complement characteristics cannot be observed ex‐ante, and argue that complementors' with larger scale and broader scope are better positioned to capture attention than smaller and less broad ones. We formalize and test this intuition in the context of news aggregators, highlighting the significance of complementors' ability to draw attention in evaluating their benefits from platform participation. Managerial Summary Small firms are often assumed to benefit most from joining a platform to expand their market reach and visibility. However, this will only be the case if the main function of platforms is to match consumer preferences to product characteristics. We argue that platforms also direct attention towards some products at the expense of others on the platform. This “attention mechanism” is particularly important whenever product characteristics cannot be observed prior to consumption, and we propose that in such settings, larger scale and broader scope of products drive attention towards specific firms on the platform. We test these predictions in the context of online news aggregators, which feature news content by newspapers of different sizes and with different range of articles. We find that indeed large and generalist newspapers benefit most from being on a news aggregators, while small and focused newspapers perform better when they are not featured on the news aggregator at all.